Immunogenicity and safety of sabin-strain based inactivated poliovirus vaccine replacing salk-strain based inactivated poliovirus vaccine: An innovative application of different strain-IPVs replacement. Issue 17 (22nd April 2021) - Chen, Haiping; Gao, Zhigang; Bai, Shuang; Liu, Xiaoqin; Han, Shasha; Xiao, Yanhui; Liu, Fang; Yu, Yinghong; Sun, Hongmei; Yang, Xiaoming
Abstract: Background: A domestic Sabin strain-based inactivated poliovirus vaccine (Sabin IPV) was approved by China Food and Drug Administration in 2017 as a replacement for the Salk strain-based inactivated poliovirus vaccine (Salk IPV) that has been in use in China for over 10 years. The present post-marketing trial was implemented in China to assess the immunogenicity and safety of replacing the Salk IPV with the Sabin IPV in the last two immunizations of the standard three-dose schedule. Methods: We conducted a randomized, controlled clinical trial with two groups that received three doses of IPVs at the age of 2, 3, and 4 months: the Salk-Sabin-Sabin group and the Salk-Salk-Salk group. Blood samples were collected before vaccination and 30–40 days after the third dose of vaccination. The seroconversion rates and antibody geometric mean titers (GMTs) were calculated and analyzed to evaluate immunogenicity. The safety of both immunization schedules was also monitored and analyzed. Results: Of 360 recruited healthy infants, all three IPV doses were administered and blood collection was completed in 330 infants. All participants (100%) in both groups were seropositive for all three poliovirus types after the last vaccination. There were significant differences between the two groups ( P < 0.001) in the GMTs for antibodies against poliovirus types 1 and 2, but no significant difference was observed for antibodies against type 3 ( P = 0.009). A non-inferiority t -test showed that the post-immunization GMTs for all three types in the Salk-Sabin-Sabin group were not inferior to those in the Salk-Salk-Salk group ( P < 0.001). Safety assessment indicated that there was no significant difference in the incidence of all adverse events between the two groups ( P = 0.806). Conclusions: The Salk-Sabin-Sabin IPV immunization schedule is not inferior to the Salk-Salk-Salk IPV schedule in terms of both immunogenicity and safety. Clinical trial number: NCT04051736.